AIRPORT PRIVATIZATION COMPETITION INCLUDING DOMESTIC AIRLINE MARKETS. Issue 1 (7th July 2016) - Kawasaki, Akio
Abstract : This study addresses the problem of hub airport privatization in a domestic airline market, where each country has one major hub airport and multiple local airports. We find that when both countries have very small domestic airline markets, airport privatization occurs at the Nash equilibrium. However, when at least one country has a large domestic airline market, the public airport becomes an equilibrium outcome. Furthermore, depending on the number of airline markets and degree of product differentiation, an asymmetric equilibrium may appear.